Contemporary Terreiro: the black people from the visitor's perspective of the Afro Brazil Museum - Santos Rodrigues, Denise (2023)
The article investigates whether the objectives of the Museological Plan of the Afro Brazil Museum are perceived by visitors, to analyze their perception of the participation of black people in the formation of Brazilian culture and society. The study used bibliographic research on theoretical concepts about museums, African and Afro-Brazilian appropriation in urban spaces, and authors such as Renato Ortiz, Néstor García Canclini, and Muniz Sodré, as well as qualitative research through focus groups and participant observation during museum visits. The analysis of the results presents the visitors' views on the experience and knowledge acquired during the visit. The research results highlight the importance of the Afro-Brazilian theme and how it can be presented in a museum, providing reflection and dialogue with visitors